Factors affecting the performance of members of the Administrative Oversight Authority and the Audit Bureau in Libya to combat corruption from their point of view (Economic studies journal, 2021)
AbstractThe study aimed to identify the factors affecting the performance of members of the Administrative Control Authority and the Accounting Bureau in Libya. Based on previous studies related to the study, the study assumed seven main factors, namely: factors related to legislation and regulations, factors related to independence (financial and administrative), factors related to the efficiency of the supervisory staff, factors related to training for the supervisory cadre, factors related to material benefits, factors related to executive procedures, and finally factors related to the bodies subject to supervision. In addition, to achieve the aim of the study, the questionnaire was used and distributed to a random sample of members of the ACA and the AB in the head quarter in Tripoli. The statistical package (SPSS), was used to analyze the data collected through the questionnaire. The results showed that, all the main factors that were studied significantly affect the performance of the members of the ACA and the AB in Libya.